Perlindungan Hak Asasi Manusia Terhadap Perdagangan Orang Dalam Kasus Lintas Negara - H, Harti; Ilmih, Andi Aina (Media Hukum Indonesia (MHI), 2024)
Crimes such as human trafficking, drug trafficking, money laundering and terrorism pose serious threats to the security and well-being of the international community. Organized transnational crime not only poses a threat to global security, but is also a highly profitable business for the perpetrators. Transnational crime, including human trafficking and human smuggling, remains a serious threat faced by almost all countries. Criminal groups involved in human trafficking often operate in hidden black markets, difficult to identify and stop. Human trafficking knows no boundaries of gender, age, status, ethnicity or nationality. Victims can come from various backgrounds and socio-economic conditions. Factors such as poverty or an unsafe living environment can increase a person's risk of becoming a target for human trafficking. Human traffickers, or what are often referred to as traffickers, use various methods and strategies to recruit victims. As globalization continues to grow stronger, the global community must face various complex issues that develop from ideology to practical impacts that occur in various regions of the country. One of the significant impacts of globalization is the emergence of various types of disturbing transnational crimes.